Sertifikat Perkawinan Analisis Maqāsid Al-Syari‘ah dan Maslahah Mursalah terhadap Peraturan Dirjen Bimas Islam No 379 Tahun 2018 - Abdur Ro’uf Hasbullah (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
This Research entitled “Marriage Certificate: Analysis of Maqāsid al-syari‘ah and Maslahah Mursalah Against Regulation of the Director General of Islamic Community Guidance No 379 of 2018”. This Research use Library Research and The Technique of Data collection use study documents relate with this topic. Furthermore, the data is analyzed using Maqāsid al-syari>‘ah and Maslahah Mursalah. The results of the research explained that the certificate as a marriage registration requirement as regulated in the Regulation of the Director General of Islamic Community Guidance No 379 of 2018 regarding Technical Guidance for Marriage Guidance for the Prospective Bride is important to be carried out and followed by the bride and groom. This sertificate as authentic evidence that the bride and groom turned out to have followed the Marriage Guidance. If it is not required to follow marital guidance, the impact will be the poorer quality of the family. Therefore, the marriage guidance program must be implemented as well as possible so that it can provide benefits to the bride and groom. Hopefully, after joining the marriage guidance program, married couples can anticipate and minimalize quarrel, violence and divorce in the family to create a family which is sakinah, mawaddah, wa raḥmah.